Implementasi Pendidikan Agama Islam Bagi Siswa Tunanetra - Sari, Lailli Irna; Wibawa, Zakki Teguh; Jaistyurohman, Robbit Azam; Alamsyah, Dani (ALSYS, 2021)
Education is an aspect that must be accepted by children so that later they are not wrong in taking steps to take the next life. Islamic religious education itself is an education that must be known by every child so that it becomes a guide for the life to come. This journal will discuss the material "Implementation of Islamic Religious Education for Blind Children". This journal was created because not many materials have been published in other journals, because many people despise blind children in doing learning which causes blind children to be underestimated by outsiders. Whereas blind children themselves have a level of intelligence that sometimes exceeds the abilities of normal children.